Fatty Infiltration of Multifidus Muscles: An Easily Overlooked Risk Factor for the Severity of Osteoporotic Vertebral Fractures - Wuyan Xu; Xiaowen Liu; Li Wu; Shaohua Liang; Ye Zhang; Junbing Huang; Xuwen Zeng; Siming Li; Fan Xu; Yuchao Xiong (Orthopaedic Surgery, 2024)
Objectives Osteoporotic vertebral fractures (OVFs) are a critical public health concern requiring urgent attention, and severe OVFs impose substantial health and economic burdens on patients and society. Analysis of the risk factors for severe OVF is imperative to actively prevent the occurrence of this degenerative disorder. This study aimed to investigate the risk factors associated with the severity of OVF, with a specific focus on changes in the paraspinal muscles. Methods A total of 281 patients with a first‐time single‐level acute OVF between January 2016 and January 2023 were enrolled in the study. Clinical and radiological data were collected and analyzed. The cross‐sectional area (CSA) and degree of fatty infiltration (FI) of the paraspinal muscles, including the multifidus muscles (MFMs), erector spinae muscles (ESMs), and psoas major muscles (PSMs), were measured by magnetic resonance imaging (MRI) of the L4/5 intervertebral discs. According to the classification system of osteoporotic fractures (OF classification) and recommended treatment plan, OVFs were divided into a low‐grade OF group and a high‐grade OF group. Univariate and multivariate logistic regression analyse s were performed to identify risk factors associated with the severity of OVF. Results Ninety‐eight patients were included in the low‐grade OF group, and 183 patients were included in the high‐grade OF group. Univariate analysis revealed a significantly higher incidence of a high degree of FI of MFMs (OR = 1.71, p = 0.002) and ESMs (OR = 1.56, p = 0.021) in the high‐grade OF group. Further multivariate logistic regression analysis demonstrated that a high degree of FI of the MFMs (OR = 1.71, p = 0.002) is an independent risk factor for the severity of OVF. Conclusion A high degree of FI of the MFMs was identified as an independent risk factor for the severity of OVF. Decreasing the degree of FI in the MFMs might lower the incidence of the severity of OVF, potentially reducing the necessity for surgical intervention in OVF patients.